THE METRIC DIMENSION OF A GRAPH COMPOSITION PRODUCTS WITH STAR - S.W. Saputro; D. Suprijanto; Edi Tri Baskoro; A.N.M. Salman (Journal of the Indonesian Mathematical Society, 2012)
looked at pdf abstractDOI : http://dx.doi.org/10.22342/jims.18.2.114.85-92